Copolymerized polyester resin, molded article, and heat-shrinkable film

CN112996837BActive Publication Date: 2026-10-30TOYOBO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN201980072717.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-10-31
Filing Date
2019-10-28
Publication Date
2026-10-30
Estimated Expiration
2039-10-28

AI Technical Summary

Technical Problem

[0007]本发明是鉴于该现有技术中的问题而提出的,解决了如下问题:在连续地生产膜和成型品时发生塑膜挤压模污染、在膜和成型品上异物附着;共聚聚酯的热稳定性和热氧化稳定性所需的再利用性;再利用时的树脂着色和分子量降低

Benefits of technology

[0010]本发明的共聚聚酯树脂可以解决如下问题:在连续地生产膜和成型品时,减少发生塑膜挤压模污染、在膜和成型品上异物附着;树脂的热稳定性和热氧化稳定性所需的再利用性;大幅降低再利用时的树脂着色。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003049809990000101
    Figure BDA0003049809990000101
  • Figure BDA0003049809990000111
    Figure BDA0003049809990000111
  • Figure BDA0003049809990000112
    Figure BDA0003049809990000112
Patent Text Reader

Abstract

The copolymer polyester resin of the present invention solves the problem of film extrusion die contamination and foreign matter attachment on films and molded articles during continuous production of films and molded articles, wherein, when the main component of the dicarboxylic acid component is terephthalic acid, the main component of the diol component is ethylene glycol, and the total diol component is 100 mol%, the content of neopentyl glycol is greater than 15 mol% and 40 mol% or less, the content of diethylene glycol is 6 to 20 mol%, the content of cyclic dimer composed of terephthalic acid, neopentyl glycol and diethylene glycol is 5000 ppm or less, and the content of cyclic trimer composed of terephthalic acid and ethylene glycol is 5000 ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a copolyester resin that has excellent transparency, color, reusability and moldability, and reduces the occurrence of mold head contamination or foreign matter adhesion. Background Technology

[0002] Polyethylene terephthalate (PET), manufactured from polyester, especially terephthalic acid (hereinafter, sometimes abbreviated as TPA) and ethylene glycol (hereinafter, sometimes abbreviated as EG), has excellent chemical and physical properties and is widely used in containers, films, sheets, fibers and other applications.

[0003] In recent years, polyesters (hereinafter referred to as copolyesters) obtained by copolymerizing neopentyl glycol (hereinafter sometimes referred to as NPG) during the manufacture of polyethylene terephthalate (PET) have attracted attention due to their excellent transparency, impact resistance, moldability, and heat resistance. They are used for various applications, especially as raw material polymers for molded materials such as films, sheets, injection molded parts, and deformed parts.

[0004] On the other hand, based on factors such as processability, environmental stability, and price competitiveness, vinyl chloride resin is used as molded parts for outdoor applications such as building materials. However, due to the potential carcinogenicity and endocrine disorders caused by the leaching of monomers and plasticizers from these molded parts, as well as the problem of generating toxic gases during incineration, the demand for alternatives to polyester resins containing polyesters obtained by copolymerizing the aforementioned NPG is constantly increasing.

[0005] To improve transparency, chemical resistance, and moldability, techniques have been proposed for obtaining copolyesters by limiting the amount of neopentyl glycol copolymerization to a specific range, and for molding articles made from the aforementioned copolyesters (see, for example, Patent Documents 1, 2, 3, 4, and 5). However, problems arise when these films are continuously produced, such as coloring and molecular weight reduction due to resin degradation. Furthermore, foreign matter adheres to the vicinity of the extrusion die, reducing the product value and causing further problems during reuse. Solutions are needed. Additionally, a technique has been proposed for improving the extrusion moldability of copolyester resins by increasing melt viscosity through copolymerization with a branched-chain introducing agent (see, for example, Patent Document 6). Existing technical documents Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 8-337659 Patent Document 2: Japanese Patent Application Publication No. 2000-109546 Patent Document 3: Japanese Patent Application Publication No. 2011-46859 Patent Document 4: Japanese Patent Application Publication No. 2011-46860 Patent Document 5: Japanese Patent Application Publication No. 2011-68879 Patent Document 6: Japanese Patent Application Publication No. 2004-27176 Summary of the Invention The problem that the invention aims to solve

[0007] The present invention addresses the problems in the prior art by solving the following issues: plastic film extrusion mold contamination and foreign matter adhesion on films and molded articles during continuous production of films and molded articles; the reusability required for the thermal and thermal oxidative stability of copolyesters; and resin coloring and molecular weight reduction during reuse. Technical solutions to the problem

[0008] To address the aforementioned issues, it was found that by producing a copolyester characterized by having a free cyclic dimer composed of terephthalic acid, neopentyl glycol, and diethylene glycol in a specific composition of the copolyester resin at a content of 5000 ppm or less, and a cyclic trimer composed of terephthalic acid and ethylene glycol at a content of 5000 ppm or less, a copolyester resin that can impart high commercial value to molded articles and films with improved continuous production efficiency and transparency can be provided. Furthermore, by using ethylene glycol, neopentyl glycol, and diethylene glycol in combination, the following trends emerge: lower crystallinity and polymer viscosity, improved film-forming properties during film formation, improved formability during molding, and improved transparency. While diethylene glycol used in this copolyester is very cost-effective, it is judged to have low thermal stability and thermal oxidative stability. Therefore, it is believed that the low thermal stability and thermal oxidative stability of the copolyester during the reuse of films and molded articles, coupled with resin degradation caused by heating during film formation and molded article manufacturing, significantly reduces the limiting viscosity and color of the films and molded articles. Next, the inventors of this invention discovered that, due to the improvement in the thermal stability and thermal oxidative stability of the copolyester resin, there is a trend towards an improvement in the carboxyl terminus concentration (AV) of the copolyester resin in the range of 8 to 25 eq / t. Furthermore, to further improve the thermal stability and thermal oxidative stability of the copolyester resin, it was considered to change the type of catalyst used in the polymerization. Moreover, instead of antimony compounds, titanium compounds, and germanium compounds as polymerization catalysts, a combination of aluminum compounds and phosphorus compounds is preferred. This improves the thermal stability and thermal oxidative stability of the resin, and the catalyst exhibits excellent activity. Therefore, even if the number-average molecular weight of the resin is reduced to increase the film-forming speed and molding speed of the molded articles and films, the number-average molecular weight of the resulting molded articles and films will not decrease significantly. The formability of the molded articles, the film-forming properties, and the strength of the films will not be affected, and the manufacturing costs of the molded articles, films, and products can be reduced.

[0009] The present invention is based on the above findings and has the following structure (1) to (9): (1) A copolyester resin, characterized in that, when the main component of the dicarboxylic acid component is terephthalic acid, the main component of the diol component is ethylene glycol, and all the diol components are set to 100 mol%, the content of neopentyl glycol is greater than 15 mol% and less than 40 mol%, the content of diethylene glycol is 6 to 20 mol%, the content of the cyclic dimer composed of terephthalic acid, neopentyl glycol and diethylene glycol is less than 5000 ppm, and the content of the cyclic trimer composed of terephthalic acid and ethylene glycol is less than 5000 ppm. (2) The copolyester resin according to (1) is characterized in that the content of the cyclic trimer composed of terephthalic acid and ethylene glycol is less than 4000 ppm. (3) The copolyester resin according to any one of (1) to (2), characterized in that the color b value of the copolyester resin is -5.0 to 10.0. (4) The copolyester resin according to any one of (1) to (3), characterized in that the concentration of carboxyl terminus AV is 8 to 25 eq / t, the copolyester resin contains aluminum atoms and phosphorus atoms, the aluminum atom content in the copolyester resin is 15 to 40 ppm, and the molar ratio of phosphorus atoms to aluminum atoms in the copolyester resin is 1.8 to 2.6. (5) The copolyester resin according to any one of (1) to (4), characterized in that the haze value at 5 mm thickness of the stepped molded plate obtained by molding the copolyester resin is 15% or less. (6) A molded article, characterized in that it contains a copolyester resin as shown in any one of (1) to (5). (7) A heat shrinkable film, characterized in that it contains any one of (1) to (5) copolyester resin. Invention Effects

[0010] The copolyester resin of the present invention can solve the following problems: reducing plastic film extrusion mold contamination and foreign matter adhesion on films and molded articles during continuous production of films and molded articles; reusability required for the thermal and thermal oxidative stability of the resin; and significantly reducing resin coloration during reuse.

[0011] In addition, molded articles and films obtained from the copolyester resin of the present invention can have reusability, heat resistance and excellent appearance. Detailed Implementation

[0012] The copolyester resin of the present invention will now be described in detail. The copolyester resin of this invention is a polyester resin in which dicarboxylic acid and diol are constituent components. When the main component of the dicarboxylic acid is terephthalic acid, the main component of the diol is ethylene glycol, and the total diol content is set at 100 mol%, the content of neopentyl glycol is greater than 15 mol% and less than 40 mol%, and the content of diethylene glycol is 6 to 20 mol%. The main component of the diol being ethylene glycol means that, in the diol composition, ethylene glycol is the most abundant component, expressed in mol%. The content of neopentyl glycol is preferably 18 to 38 mol%, more preferably 20 to 36 mol%. The content of diethylene glycol is preferably 7 to 19 mol%, more preferably 8 to 16 mol%.

[0013] In this invention, the following compounds are referred to as a cyclic dimer composed of terephthalic acid, neopentyl glycol, and diethylene glycol, and a cyclic trimer composed of terephthalic acid and ethylene glycol. The former is a cyclic dimer synthesized sequentially by bonds of terephthalic acid, neopentyl glycol, terephthalic acid, and diethylene glycol (hereinafter referred to as T2N1D1), and the latter is a cyclic trimer synthesized by bonds of terephthalic acid and ethylene glycol in alternating three bonds (hereinafter referred to as CT). The T2N1D1 content is 5000 ppm or less, and the CT content is 5000 ppm or less. In this invention, "copolyester resin" refers to a substance that contains not only a chemical substance called polyester, but also oligomer components called T2N1D1 and CT, and a catalyst component described later. However, for convenience, the chemical substance called polyester is sometimes referred to as "copolyester resin".

[0014] When the content of neopentyl glycol and diethylene glycol is less than the above range, the transparency of the molded body and film deteriorates due to crystallization, failing to achieve sufficient transparency and thus tending to lose commercial value. To clarify, here, amorphous refers to the absence of a melting peak in either of the following heating processes: a sample obtained by placing it at 120°C for 120 minutes using a Yamato DP63 dryer; a sample that has been heated to -100°C to 300°C at a rate of 20°C / min; a sample that has been cooled to -100°C at a rate of 50°C / min; and a sample that has been heated to -100°C to 300°C at a rate of 20°C / min; and a sample that has been heated to -100°C to 300°C at a rate of 20°C / min. The copolyester resin of this invention is amorphous, thus ensuring sufficient transparency even in thick-walled molded bodies. That is, "amorphous" as used under these testing conditions indicates that the transparency of the film can be maintained to a high standard, and sufficient transparency can be maintained even when the film is made into a thick-walled film. Furthermore, due to the increased CT content, contamination becomes severe near the resin outlet of the extrusion die in the film extrusion molding machine and the mold in the injection molding machine during continuous film formation and molding. Foreign matter adheres to the surface of the molded body, leading to a decrease in product value. Additionally, exceeding the aforementioned limits results in an increase in free T2N1D1, leading to severe contamination near the resin outlet of the film extrusion die in the film extrusion molding machine and the mold in the injection molding machine during continuous film formation and molding. Foreign matter adheres to the surface of the film and the molded body, further reducing product value. Although the adhesion mechanism is not yet clear, it is believed to be due to the influence of diethylene glycol in T2N1D1, which has a lower melting point and glass transition temperature, thus increasing adhesion. T2N1D1 acts as a binder, resulting in increased adhesion during molding and at the film extrusion die in the film extrusion molding machine.

[0015] The content of T2N1D1 is preferably 4500 ppm or less, more preferably 4000 ppm or less. When it exceeds 5000 ppm, contamination near the resin outlet of the extrusion die in the extrusion molding machine becomes severe during film production. Foreign matter adheres to the surface of the molded article, deteriorating its surface condition and affecting transparency, thus reducing its commercial value. Furthermore, during continuous injection molding, the venting port of the injection mold becomes blocked, preventing the production of a normal molded article. From an economic perspective during production, the lower limit of this content is 1000 ppm. The content of T2N1D1 is a value obtained quantitatively using the measurement method described in the examples below.

[0016] The preferred CT content is 4500 ppm, more preferably 4000 ppm or less. When it exceeds 5000 ppm, contamination near the resin outlet of the extrusion die in the film extrusion molding machine becomes severe during film production. Foreign matter adheres to the surface of the molded body, deteriorating its surface condition and affecting transparency, thus reducing its commercial value. Furthermore, during continuous injection molding, the venting ports of the injection mold become blocked, preventing the production of a properly formed molded body. From an economic perspective during production, the lower limit for this content is 1000 ppm.

[0017] The main dicarboxylic acid component of the copolyester resin of the present invention is terephthalic acid. The proportion of terephthalic acid to the total dicarboxylic acid is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, and most preferably 100 mol%.

[0018] Other dicarboxylic acid components that can be used with terephthalic acid include: (1) aromatic dicarboxylic acids and their functional derivatives such as isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyl-4,4'-dicarboxylic acid and diphenoxyethanedicarboxylic acid; (2) aliphatic dicarboxylic acids and their functional derivatives such as adipic acid, sebacic acid, succinic acid, glutaric acid, dimer acid, dodecanedicarboxylic acid, azelaic acid; and (3) alicyclic dicarboxylic acids and their functional derivatives such as hexahydroterephthalic acid, hexahydroisophthalic acid, and cyclohexanedicarboxylic acid.

[0019] The copolyester resin of the present invention preferably consists entirely of ethylene glycol, neopentyl glycol, and diethylene glycol as its glycol composition. However, other glycol compositions may be used to impart additional functions or improve properties, provided that they do not impair the various properties intended for the purposes of the present invention. The total amount of ethylene glycol, neopentyl glycol, and diethylene glycol relative to the total glycol composition is preferably 70 mol% or more, more preferably 85 mol% or more, particularly preferably 95 mol% or more, and most preferably 100 mol%.

[0020] Other diol components include (1) aliphatic diols such as trimethylene glycol, tetramethylene glycol, pentamethylene glycol, and hexamethylene glycol; (2) alicyclic diols such as 1,3-cyclohexanediethanol and 1,4-cyclohexanediethanol; and (3) aromatic diols such as p-xylenediol and m-xylenediol. Among these, 1,4-cyclohexanediethanol is preferred. In addition, these diol components can be used alone or in combination of two or more in any proportion.

[0021] In the copolyester resin of the present invention, from the viewpoint of improving the extrusion molding properties of profiles, it is preferable that the copolyester resin contains 0.001 to 5 mol of a polyfunctional compound having 3 or more carboxyl groups, hydroxyl groups or their ester-forming groups (e.g., trimellitic acid, pyromellitic acid, glycerol, trimethylolpropane, etc.) as the acid component and / or diol component.

[0022] The copolyester resin of the present invention can be produced by a manufacturing method utilizing direct esterification and polycondensation reactions, or by a manufacturing method utilizing transesterification and polycondensation reactions. The above reactions can be carried out in a batch reactor or a continuous reactor; from the perspective of economy and quality stability, a continuous reactor is preferred.

[0023] In a continuous reaction apparatus (continuous polycondensation method), esterification, transesterification, and melt polycondensation can each be carried out in one step, or preferably in multiple steps. When esterification or transesterification is carried out in multiple steps, the number of reaction vessels is preferably 2 to 3. Similarly, when melt polycondensation is carried out in multiple steps, the number of reaction vessels is preferably 3 to 7.

[0024] In manufacturing the copolyester resin of the present invention by continuous polycondensation, a slurry is prepared, wherein the total diol contained in the slurry is 1.02 to 1.5 moles, preferably 1.03 to 1.4 moles, relative to 1 mole of total dicarboxylic acid or its ester derivatives, and this slurry is continuously supplied to an esterification reaction step containing oligomers. Typically, the esterification reaction temperature is 240 to 270°C, preferably 250 to 265°C. Furthermore, the pressure inside the reaction vessel is typically 0.2 MPa or less, preferably 0.01 to 0.05 MPa. Additionally, the polycondensation reaction temperature is typically 265 to 285°C, preferably 270 to 280°C, and the pressure inside the reaction vessel is typically 1.5 hPa or less, preferably 0.5 hPa or less. The reaction time of the esterification reaction is preferably 5 hours or less, particularly preferably 2 to 3.5 hours. Furthermore, the reaction time of the polycondensation reaction is preferably 3 hours or less, particularly preferably 1 to 2 hours.

[0025] When manufacturing the copolyester resin of the present invention by intermittent polycondensation, the esterification reaction temperature is typically 220–250°C, preferably 230–245°C. Furthermore, the pressure inside the reaction vessel is typically 0.2–0.4 MPa, preferably 0.25–0.30 MPa. The polycondensation reaction can be carried out in one step or in multiple steps. When carried out in one step, the pressure is gradually reduced and the temperature is gradually increased, with the final temperature set in the range of 260–280°C, preferably 265–275°C, and the final pressure typically set below 3 hPa, preferably below 0.5 hPa. The reaction time for the esterification reaction is preferably 4 hours or less, particularly preferably 2–3 hours. Furthermore, the reaction time for the polycondensation reaction is preferably 5 hours or less, particularly preferably 1–3 hours.

[0026] Next, in the production of oligomers via a continuous transesterification reaction, a solution containing dimethyl terephthalate and a diol is prepared, wherein the diol is present in a concentration of 1.1 to 1.6 moles, preferably 1.2 to 1.5 moles, relative to 1 mole of dimethyl terephthalate. This solution is continuously supplied to the transesterification reaction step. The transesterification reaction temperature is typically 200 to 270°C, preferably 230 to 265°C. In addition to the polycondensation catalyst, a transesterification catalyst is also required during the transesterification process. The resulting oligomers are reacted in the same manner as the continuous polycondensation process described above.

[0027] In addition, when producing oligomers via a batch transesterification reaction, dimethyl terephthalate and a glycol are added to a batch reactor, wherein the glycol is 2.3 to 2.0 moles, preferably 2.2 to 2.0 moles, relative to 1 mole of dimethyl terephthalate, and the reaction is carried out in the presence of a transesterification catalyst. The resulting oligomer is polycondensed in the same manner as the esterification reaction described above.

[0028] As a polycondensation catalyst, at least one of antimony compounds, germanium compounds, titanium compounds, and aluminum compounds can be used. Examples of the aforementioned antimony compounds include antimony trioxide, antimony pentoxide, antimony acetate, and antimony glycolate. Antimony trioxide, antimony acetate, and antimony glycolate are preferred, with antimony trioxide being particularly preferred. These antimony compounds preferably contain 50 to 400 ppm, more preferably 100 to 350 ppm, and particularly preferably 150 to 300 ppm, relative to the resulting copolyester resin.

[0029] In addition, examples of the aforementioned germanium compounds include crystalline germanium dioxide, amorphous germanium dioxide, germanium tetroxide, germanium hydroxide, germanium oxalate, germanium chloride, germanium tetraethoxy, germanium tetrabutoxy, and germanium phosphite. Among these, crystalline germanium dioxide and amorphous germanium dioxide are more preferred, and amorphous germanium dioxide is particularly preferred. The content of these germanium compounds in the resulting copolyester resin is preferably 10 to 100 ppm, more preferably 30 to 70 ppm, and particularly preferably 30 to 50 ppm.

[0030] In addition, the titanium compounds mentioned above include, for example, tetraalkyl titanates such as tetraethyl titanate, tetraisopropyl titanate, tetran-propyl titanate, and tetran-butyl titanate, and their partial hydrolysis products; titanium oxalate compounds such as titanium acetate, oxalate oxide, ammonium oxalate, sodium oxalate, potassium oxalate, calcium oxalate, and strontium oxalate; titanium trimellitate, titanium sulfate, titanium chloride, hydrolysates of titanium halides, titanium bromide, titanium fluoride, potassium hexafluorotitanate, ammonium hexafluorotitanate, cobalt hexafluorotitanate, manganese hexafluorotitanate, titanium acetylacetonate, complexes of titanium with hydroxy polycarboxylic acids or nitrogen-containing polycarboxylic acids, composite oxides composed of titanium and silicon or zirconium, and reactants of alkoxy titanium with phosphorus compounds. Among these, titanium tetraisopropoxide, titanium tetrabutoxide, and potassium oxalate are preferred, and titanium tetrabutoxy is particularly preferred. These titanium compounds preferably contain 1 to 50 ppm, more preferably 2 to 20 ppm, and particularly preferably 3 to 10 ppm, relative to the resulting copolyester resin.

[0031] Aluminum compounds are preferred as polymerization catalysts due to their reusability (heat resistance, thermal oxidation stability). Aluminum compounds are preferably used in combination with phosphorus compounds. There are no limitations on the aluminum compound used as the polymerization catalyst constituting the copolyester resin used in the manufacture of the present invention; known aluminum compounds can be used.

[0032] Specifically, aluminum compounds include aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, aluminum acetylacetonate, aluminum oxalate, and other organoaluminum compounds and their partial hydrolysates. Among these, carboxylates, inorganic acid salts, and chelating compounds are preferred; more preferably, aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, and aluminum acetylacetonate; further preferred, aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, and aluminum hydroxychloride; and most preferably, aluminum acetate and basic aluminum acetate.

[0033] Regarding the amount of aluminum compound used in the polymerization catalyst, the residual amount of aluminum atoms relative to the total mass of the obtained polyester resin is preferably 15 to 40 ppm, more preferably 17 to 38 ppm, and even more preferably 20 to 35 ppm. When the residual amount of aluminum atoms is less than the above range, poor catalytic activity may occur. On the other hand, when the residual amount of aluminum atoms exceeds the above range, problems may arise due to decreased thermal stability and thermal oxidation stability, as well as increased foreign matter generation and coloring caused by aluminum. It should be noted that, as described above, during polyester polymerization, even if the aluminum compound is placed under reduced pressure, the amount used as a polymerization catalyst is essentially 100% residual, so the amount used can be considered as the residual amount.

[0034] The phosphorus compound used in the polymerization catalyst is not particularly limited, but the catalytic activity is significantly improved when phosphonic acid compounds or hypophosphonic acid compounds are used, and therefore preferred. Among them, the improvement in catalytic activity is particularly significant when phosphonic acid compounds are used, and therefore even more preferred.

[0035] Among these phosphorus compounds, those containing a phenolic moiety within the same molecule show a significant improvement in the resin's thermal and thermal oxidative stability, and are therefore preferred. Any phosphorus compound with a phenolic structure is acceptable and is not particularly limited, but when one or more compounds selected from phosphonic acid compounds and hypophosphonic acid compounds containing a phenolic moiety within the same molecule are used, both the improvement in catalytic activity and the improvement in the resin's thermal and thermal oxidative stability are significant, and therefore are preferred. Among these, the use of one or more phosphonic acid compounds containing a phenolic moiety within the same molecule shows a particularly significant improvement in both catalytic activity and the improvement in the resin's thermal and thermal oxidative stability, and is therefore particularly preferred.

[0036] In addition, as phosphorus compounds having a phenolic moiety within the same molecule, compounds represented by the following general formulas (1) and (2) can be listed.

[0037] [Chemistry 1] P(=O)R 1 (OR 2 (OR) 3 General formula (1)

[0038] [Chemistry 2] P(=O)R 1 R 4 (OR 2 General formula (2)

[0039] (In general formulas (1) to (2), R) 1R represents a hydrocarbon group containing 1 to 50 carbon atoms of the phenolic moiety, or a hydrocarbon group containing 1 to 50 carbon atoms of the phenolic moiety, or a substituent such as a hydroxyl or halogen group, or an alkoxy or amino group. 4 R represents a hydrogen atom, a hydrocarbon group with 1 to 50 carbon atoms, or a hydrocarbon group with 1 to 50 carbon atoms containing substituents such as hydroxyl, halogen, alkoxy, or amino groups. 2 R 3 Each of these groups independently represents a hydrogen atom, a hydrocarbon group with 1 to 50 carbon atoms, or a hydrocarbon group with 1 to 50 carbon atoms containing substituents such as hydroxyl or alkoxy groups. The hydrocarbon group can include branched structures, alicyclic structures such as cyclohexyl, or aromatic ring structures such as phenyl or naphthyl. R 2 and R 4 The ends can bond together.

[0040] Examples of phosphorus compounds containing a phenolic moiety within the same molecule, as described above, include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphonic acid, methyl bis(p-hydroxyphenyl)phosphonate, phenyl bis(p-hydroxyphenyl)phosphonate, p-hydroxyphenylphenylphosphonic acid, methyl p-hydroxyphenylphenylphosphonate, phenyl p-hydroxyphenylphenylphosphonate, p-hydroxyphenylphosphonic acid, methyl p-hydroxyphenylphosphonate, and phenyl p-hydroxyphenylphosphonate. Additionally, phosphorus compounds represented by the following general formula (3) can be included.

[0041] [Chemistry 3]

[0042] In general formula (3), X1 and X2 represent hydrogen atoms, alkyl groups with 1 to 4 carbon atoms, or metals with a valence of 1 or higher, respectively. Alternatively, the metal of X1 can have a valence of 2 or higher, while X2 may not be present. Furthermore, for phosphorus compounds, an anion with a residual valence equivalent to that of the metal can also be prepared. As metals, Li, Na, K, Ca, Mg, and Al are preferred.

[0043] When phosphorus compounds containing phenolic moieties within the same molecule are added during the polymerization of polyester, the catalytic activity of the aluminum compounds is enhanced, and the thermal and thermal oxidative stability of the resulting polyester resin is also improved. The reasoning is as follows: the hindered phenolic moieties in the phosphorus compounds improve the thermal and thermal oxidative stability of the polyester resin. However, when the residual amount of the phosphorus compound is less than 31 ppm, the aforementioned improvement in thermal and thermal oxidative stability is weaker. As a result, the improvement in thermal and thermal oxidative stability, as well as the improvement in coloring, of the polyester resin of the present invention is sometimes not observed.

[0044] In the above, the phosphorus compound preferably used as a polycondensation catalyst is at least one phosphorus compound selected from the compounds represented by the following chemical formulas (4) and (5).

[0045] [Chemistry 4]

[0046] [Chemistry 5]

[0047] As a compound represented by the above chemical formula (4), Irganox1222 (manufactured by BASF Corporation) is commercially available. In addition, as a compound represented by chemical formula (5), Irganox1425 (manufactured by BASF Corporation) is commercially available, and both can be used.

[0048] The amount of phosphorus compound used in the polymerization catalyst is preferably 31 to 119 ppm, more preferably 39 to 105 ppm, and even more preferably 48 to 92 ppm, in the form of phosphorus atoms, relative to the total mass of the obtained copolyester resin. When the amount of phosphorus atoms remaining exceeds the above-mentioned upper and lower limits, the polymerization activity may sometimes decrease. It should be noted that, as mentioned above, when the phosphorus compound is placed under reduced pressure during the polymerization of the polyester resin, it is removed from the system as part of the amount of catalyst initially added to the system, but this removal amount is almost a constant proportion, so it can be said that it is appropriate to consider the residual amount as a removal proportion.

[0049] Furthermore, as mentioned above, the ratio of phosphorus compounds to aluminum compounds is also important in this invention. Specifically, in this invention, the molar ratio (P / Al ratio) of phosphorus atoms to aluminum atoms in the polyester resin is required to be 1.8 to 2.6, preferably 2.0 to 2.4, and more preferably 2.1 to 2.3. Aluminum compounds alone, when used as polymerization catalysts, cannot fully exert their catalytic activity. By using phosphorus compounds in combination with aluminum compounds at specific ratios as polymerization catalysts, the catalytic activity can be significantly improved. When the molar ratio of phosphorus atoms to aluminum atoms in the polyester resin is outside the above range, it may not be able to fully function as a polymerization catalyst.

[0050] In this invention, without impairing the effects of the invention, in addition to the aforementioned aluminum and phosphorus compounds, metal-containing polycondensation catalysts such as titanium compounds, tin compounds, and germanium compounds can be used in combination to further enhance catalytic activity. In this case, the mass ratio of germanium compound to the obtained polyester resin is preferably 10 ppm or less, the mass ratio of titanium compound to the obtained polyester resin is preferably 3 ppm, and the mass ratio of tin compound to the obtained polyester resin is preferably 3 ppm or less. For the purposes of this invention, it is preferable to avoid using these metal-containing polycondensation catalysts such as titanium compounds, tin compounds, and germanium compounds as much as possible. Furthermore, antimony compounds, which are typically used as polymerization catalysts, have poor effects on improving the thermal stability and thermal oxidative stability of the aforementioned resins, and therefore should not be used in this invention.

[0051] Furthermore, in the manufacture of the copolyester resin of the present invention, alkali metal compounds or alkaline earth metal compounds can be used in combination. Examples of alkali metal compounds or alkaline earth metal compounds include carboxylates such as acetates and alkoxides of these elements, which are prepared as powders, aqueous solutions, ethylene glycol solutions, etc., and added to the reaction system.

[0052] In the case of direct esterification, the aforementioned polycondensation catalyst can be added at any time, either before the start of the esterification reaction or after the completion of the pressurized esterification reaction, until the start of the initial polycondensation reaction. However, when using antimony or titanium compounds as polycondensation catalysts, it is preferable to add them before the esterification reaction. Furthermore, other polycondensation catalysts, heat stabilizers, and additives are preferably added after the esterification reaction.

[0053] Furthermore, in the case of transesterification, the aforementioned polycondensation catalyst can be added at any time before the start of the transesterification reaction or until the start of the initial polycondensation reaction. However, since titanium compounds function not only as polycondensation catalysts but also as transesterification catalysts, it is preferable to add them before the start of the transesterification reaction. Additionally, other polycondensation catalysts, heat stabilizers, and additives are preferably added after the transesterification reaction is complete. As transesterification catalysts, titanium compounds such as manganese acetate, magnesium acetate, and titanium tetrabutoxide are preferred. The transesterification catalyst needs to be added before the start of the transesterification reaction.

[0054] In addition, when using catalysts other than the aforementioned aluminum compounds, phosphorus compounds can be used as stabilizers. Examples of phosphorus compounds include phosphoric acid, phosphorous acid, phosphonic acid, and their derivatives. Preferred examples include phosphoric acid, trimethyl phosphate, tributyl phosphate, triphenyl phosphate, monomethyl phosphate, dimethyl phosphate, monobutyl phosphate, dibutyl phosphate, phosphorous acid, trimethyl phosphite, tributyl phosphite, methylphosphonic acid, dimethyl methylphosphonate, dimethyl ethylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, and diphenyl phenylphosphonate. Trimethyl phosphate and phosphoric acid are particularly preferred. These phosphorus compounds are preferably present in a concentration of 1 to 100 ppm relative to the resulting copolyester, more preferably 3 to 70 ppm, and particularly preferably 5 to 50 ppm.

[0055] To improve the hue of copolyester resins, cobalt compounds can be incorporated. Adding cobalt compounds particularly reduces the color b-value. The cobalt compound needs to contain 0.5 to 30 ppm of cobalt atoms relative to the copolyester resin, more preferably 1 to 20 ppm, and particularly preferably 1 to 15 ppm. When the cobalt atom content exceeds the above range, the copolyester resin darkens or turns bluish due to the reduction of cobalt metal, resulting in a color L-value less than 50 and a color b-value less than -5, thus reducing its commercial value. Examples of cobalt compounds include cobalt acetate, cobalt chloride, cobalt benzoate, and cobalt chromate. Cobalt acetate is preferred.

[0056] The copolyester resin obtained by the above-mentioned continuous or intermittent polycondensation method is usually drawn out in a linear fashion from the extraction port located at the bottom of the reaction vessel, cooled with water, and then cut into small pieces or sheets.

[0057] The copolyester resin of the present invention, containing a low content of free T2N1D1 and CT, can be manufactured by the following method. Preferably, it is a method of polycondensation reaction by adding a specific diol component during or after esterification or transesterification. The specific diol component is preferably neopentyl glycol and diethylene glycol, more preferably neopentyl glycol. For example, taking into account the amount of raw material monomers to be added, an esterification or transesterification reaction is carried out beforehand, and diethylene glycol is added during the reaction. After the reaction, neopentyl glycol and diethylene glycol are added separately, and the mixture is stirred for at least 5 minutes to carry out polycondensation. The additionally added diols are preferably 1 to 10 mol% of the total diol composition. In addition, considering the amount of raw material monomers to be added, esterification or transesterification reactions are carried out beforehand, and neopentyl glycol and diethylene glycol are added during the reaction. Neopentyl glycol is added again after the reaction, and polycondensation is carried out after stirring for at least 5 minutes. The additional added diols are preferably 1-10 mol% of the total diol composition. Furthermore, taking into account the amount of raw material monomers to be added, an esterification or transesterification reaction is carried out beforehand, and diethylene glycol is added during the reaction. Neopentyl glycol is added after the reaction, and polycondensation is carried out after stirring for more than 5 minutes. The additional added diol is preferably 1-10 mol% of the total diol content. It is believed that by adding a specific diol component and stirring during or after the esterification or transesterification reaction, the cyclic T2N1D1 and CT that have been generated by the esterification or transesterification reaction can be opened during the polycondensation reaction, thereby reducing the amount of T2N1D1 and CT.

[0058] The copolyester resin obtained as described above preferably corresponds to a terminal carboxyl group concentration of 8 to 25 equivalents or less per ton of polymer. The terminal carboxyl group concentration is preferably 23 equivalents / ton or less. Maintaining the terminal carboxyl group concentration within the above range helps to suppress coloration of the copolyester resin.

[0059] The number-average molecular weight of the copolyester resin of the present invention is preferably 15,000 to 30,000, more preferably 17,000 to 28,000, and even more preferably 18,000 to 27,000. When the number-average molecular weight is less than the above range, the crystallinity increases, resulting in increased haze, and the resin coagulation is insufficient. Therefore, the strength and elongation of the molded article are insufficient, leading to brittleness and sometimes making it unusable. On the other hand, when the above range is exceeded, the melt viscosity increases excessively, the optimal temperature in various molding processes also increases, the thermal stability deteriorates, and the film-forming properties of the sheet decrease. Furthermore, the increase of T2N1D1 and CT as described above results in decreased transparency of the molded article.

[0060] The glass transition temperature of the copolyester resin of the present invention is preferably 40°C or higher and less than 120°C, more preferably 45°C or higher and less than 115°C, and most preferably 50°C or higher and less than 110°C. It should be noted that the glass transition temperature here refers to the value measured using a differential scanning calorimeter (DSC) at a temperature increase of 20°C / min. When the glass transition temperature is below the above range, the problem of deformation of the film or the extruded molded product increases when used outdoors in summer, or when transported and stored in a closed environment in summer.

[0061] The color b-value of the copolyester resin of the present invention is preferably -5.0 to 10.0, more preferably -3.0, and even more preferably -2.5. When the color b-value exceeds the upper limit, the yellowness of the copolyester resin becomes stronger, which is not preferred in terms of hue. On the other hand, when the color b-value is greater than -5.0 in the negative direction, the blue hue of the copolyester resin becomes obvious, and it may be unusable depending on the application.

[0062] When the copolyester resin of the present invention is molded into a stepped molding plate, the haze value at the 5mm position of the stepped molding plate when the mold temperature is 10°C is preferably 15% or less, more preferably 13% or less, and particularly preferably 10% or less. When the haze value exceeds the above values, the transparency of the molded article and the film deteriorates, and it may not be usable in applications where strict transparency is required.

[0063] In the copolyester resin of the present invention, other components may be added appropriately according to the intended use. For example, impact enhancers, fillers, ultraviolet absorbers, surface treatment agents, lubricants, light stabilizers, pigments, antistatic agents, antibacterial agents, crosslinking agents, sulfur-based antioxidants, flame retardants, plasticizers, processing aids, foaming agents, etc., may be added. Generally, the copolyester of the present invention is suitable for molding into various molded bodies by blow molding, extrusion molding, injection molding, profile extrusion molding, calendering, etc., using PET, polyvinyl chloride, etc. Example

[0064] The present invention will now be specifically described through examples, but the invention is not limited thereto. It will be noted that the properties of the copolyester resin were measured according to the following method.

[0065] 1) Number-average molecular weight Using tetrahydrofuran as solvent and polystyrene as the test standard, the determination was performed by Waters gel permeation chromatography. The polystyrene equivalent was obtained using chloroform as the eluent.

[0066] 2) Intrinsic viscosity (IV) of copolyester resin Accurately weigh 0.1 g of the sample dried at 60 °C for 24 hours and dissolve it in 25 mL of a mixed solvent of phenol / tetrachloroethane (3 / 2 (mass ratio)). Measure the viscosity using an Ostwald viscometer at 30 °C.

[0067] 3) T2N1D1 content 50 mg of copolyester resin was dissolved in 1 mL of a hexafluoroisopropanol / chloroform mixed solution (volume ratio = 1 / 9), and further diluted with 4 mL of chloroform. 10 mL of methanol was added to precipitate the polymer, followed by centrifugation. The supernatant was concentrated to dryness, then dissolved in 0.4 mL of dimethylformamide, and the content of T2N1D1 was determined by high-performance liquid chromatography (HPLC). Device: Waters ACQUITYUPLC Chromatographic column: Waters BEH-C182.1×150mm (manufactured by Waters)

[0068] 4) CT content The CT content was determined by high-performance liquid chromatography using the same method as the T2N1D1 content determination method described above.

[0069] 5) Composition ratio of copolyester resin Approximately 5 mg of the copolyester resin sample was dissolved in 0.7 ml of a mixed solution of deuterated chloroform and trifluoroacetic acid (volume ratio 9 / 1), and then... 1 The measurements were performed using H-NMR (manufactured by Varian, UNITY 50).

[0070] 6) Hue The color of the polypolyester resin sheet was measured using a colorimeter (manufactured by Nippon Denshoku Co., Ltd., ZE-6000) to determine the b-value.

[0071] 7) Haze value Using an injection molding machine (M-150C-DM manufactured by Meiki Seisakusho Co., Ltd.), the copolyester resin was melted at 280°C, and a stepped molded plate with a thickness of 2 to 11 mm was formed at a mold temperature of 10°C. The haze value (%) at the 5 mm thickness position was measured by a haze meter (Nippon Denshoku Co., Ltd., model NDH2000).

[0072] 8) Molding test (evaluation of film formation on sheet) A dried copolyester resin sample was added to an extruder equipped with a sheet extrusion die, and sheets with a thickness of approximately 0.5 mm were continuously formed for 2 days. The contamination adhesion at the die exit and the condition of the sheet surface were evaluated visually according to the following criteria. (Evaluation Criteria) ◎: There is almost no contaminant adhesion at the plastic film extrusion die exit, and the sheet surface is in good condition. ○: Only trace amounts of contaminants were present at the exit of the plastic film extrusion die, and the surface condition of the sheet was good. △: A small amount of contaminants are present at the exit of the plastic film extrusion die, and a small amount of foreign matter is present on the surface of the sheet. ×: The contaminants adhering to the plastic film extrusion die outlet are very serious, and there are many deposits on the surface of the sheet.

[0073] 9) DSC determination of copolyester resin Using a differential scanning calorimeter (DSC), confirm whether a melting peak appears in a sample that has been placed at 120°C for 120 minutes in a Yamato DP63 dryer, and then heated at 20°C / min to -100°C to 300°C, followed by a cooling at 50°C / min to -100°C, and then a second heating at 20°C / min to -100°C to 300°C. Copolyesters that do not show a melting peak in either of the two heating processes are marked as "○", and copolyesters that show a melting peak in either or both processes are marked as "×".

[0074] 10) Thermal stability evaluation: Thermal oxidative decomposition parameters (TD) 3g of dried copolyester resin sheets were placed in a glass test tube and immersed in an oil bath at 280°C for 120 minutes under a nitrogen atmosphere to melt it. Calculate using the following formula. Measurement of [IV] after heating f1 TD is calculated as follows. However, [IV] i and [IV] f1 These refer to the IV (dL / g) after the heating test and the IV after the heating test, respectively. TD = 0.245{[IV] f1 -1.47 -[IV] i -1.47} The thermal oxidative decomposition parameter (TD) of copolyesters indicates that the smaller the value, the higher the thermal stability.

[0075] (Example 1) In a first esterification reactor pre-containing reactants, a slurry prepared as follows is continuously fed: high-purity terephthalic acid (TPA) is used as the dicarboxylic acid component, and ethylene glycol (EG) and neopentyl glycol (NPG) are used as diol components, with a total diol molar ratio (G / A) of 2.2 relative to the dicarboxylic acid component. The esterification reaction is then carried out under stirring at a reactor pressure of 0.15 MPa and a temperature of 257°C, with an average retention time of 3 hours. The reactants are then transferred to a second esterification reactor, where esterification is carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C, with an average retention time of 1 hour. Finally, the esterified reactants are transferred to a third esterification reactor, where esterification is carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C.

[0076] Add neopentyl glycol and diethylene glycol in amounts equivalent to 20% of the amounts added before the esterification reaction to the generated oligomers to make them consistent with the target composition, and allow the reaction to proceed for at least 15 minutes.

[0077] In the esterification reaction product, a certain amount of ethylene glycol solution of aluminum compound (basic aluminum acetate) and ethylene glycol solution of phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added and continuously fed into the first polycondensation reactor. The mixture was stirred at 261°C and 6.7 kPa for 1 hour. Then, in the second polycondensation reactor, the mixture was stirred at 272°C and 0.6 kPa for 1 hour. Finally, in the final reactor, the polycondensation reaction was carried out at 275°C and 0.10–0.20 kPa for 1 hour with stirring. After the polycondensation reaction, the reactants were passed through a polymer filter, and the molten copolymer was taken out from the nozzle of the die head in a stranded shape. After being water-cooled in a cooling bath, it was cut into small pieces. The number average molecular weight was 19,000.

[0078] The evaluation results are shown in Table 1. The copolyester resin obtained in the examples was evaluated by sheet molding using method 8), and the moldability was good.

[0079] (Examples 2-5) The reaction was carried out in the same manner as in Example 1 to obtain a copolyester resin. The evaluation results are shown in Table 1. The copolyester resin obtained in this example was evaluated by sheet molding using method 8), and the moldability was good.

[0080] (Example 6) In a first esterification reactor pre-containing reactants, a slurry prepared as follows is continuously fed: high-purity terephthalic acid (TPA) is used as the dicarboxylic acid component, and ethylene glycol (EG) and neopentyl glycol (NPG) are used as diol components, with the total diol component relative to the dicarboxylic acid component (G / A) prepared to be 1.6. Then, the esterification reaction is carried out under stirring at a reactor pressure of 0.15 MPa and a temperature of 257°C, with an average retention time of 3 hours. The reactants are then transferred to a second esterification reactor, where esterification is carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C, with an average retention time of 1 hour. Finally, the esterified reactants are transferred to a third esterification reactor, where esterification is carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C.

[0081] Add neopentyl glycol and diethylene glycol in amounts equivalent to 20% of the amounts added before the esterification reaction to the generated oligomers to make them consistent with the target composition, and allow the reaction to proceed for at least 15 minutes.

[0082] In the esterification reaction product, a certain amount of ethylene glycol solution of aluminum compound (basic aluminum acetate) and ethylene glycol solution of phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added and continuously fed into the first polycondensation reactor. The polycondensation reaction was carried out for 1 hour at 261°C and 6.7 kPa with stirring. Then, in the second polycondensation reactor, the polycondensation reaction was carried out for 1 hour at 272°C and 0.6 kPa with stirring. Finally, in the final reactor, the polycondensation reaction was carried out for 1 hour at 275°C and 0.10-0.20 kPa with stirring. After the polycondensation reaction, the reactants were passed through a polymer filter, and the molten copolymer was taken out from the nozzle of the die head in a stranded shape. After being cooled in a cooling bath, it was cut into small pieces. A copolyester resin with a number average molecular weight of 20,000 and a polymer carboxyl end group concentration of 24 eq / t was obtained. The evaluation results are shown in Table 1. The copolyester resin obtained in this embodiment was evaluated by sheet molding using method 8). It showed good formability, a resin color of 4.5, and a thermal stability of 0.11, which was found to be slightly reduced.

[0083] (Example 7) In a first esterification reactor pre-containing reactants, a slurry prepared as follows is continuously fed: high-purity terephthalic acid (TPA) is used as the dicarboxylic acid component, and ethylene glycol (EG) and neopentyl glycol (NPG) are used as the diol components, with a total diol molar ratio (G / A) of 2.2 relative to the dicarboxylic acid component. The esterification reaction is then carried out under stirring at a reactor pressure of 0.15 MPa and a temperature of 257°C, with an average retention time of 3 hours. The reactants are then transferred to a second esterification reactor, where esterification is carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C, with an average retention time of 1 hour. Finally, the esterified reactants are transferred to a third esterification reactor, where esterification is carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C.

[0084] Add neopentyl glycol and diethylene glycol in amounts equivalent to 20% of the amounts added before the esterification reaction to the generated oligomers to make them consistent with the target composition, and allow the reaction to proceed for at least 15 minutes.

[0085] In the esterification reaction product, a certain amount of ethylene glycol solution of aluminum compound (basic aluminum acetate) and ethylene glycol solution of phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added and continuously fed into the first polycondensation reactor. The mixture was stirred at 261°C and 6.7 kPa for 1 hour. Then, in the second polycondensation reactor, the mixture was stirred at 272°C and 0.6 kPa for 1 hour. Finally, in the final reactor, the polycondensation reaction was carried out at 275°C and 0.10–0.20 kPa with stirring for 0.9 hours. After the polycondensation reaction, the reactants were passed through a polymer filter, and the molten copolymer was taken out from the nozzle of the die head in a stranded shape. After being water-cooled in a cooling bath, it was cut into small pieces. A copolyester resin with a number average molecular weight of 16,000 was obtained. The evaluation results are shown in Table 1. The copolyester resin obtained in this embodiment was evaluated by sheet molding using method 8). It showed good formability, and the haze of the stepped molded plate was 12.0, which was found to be slightly reduced.

[0086] (Example 8) In a first esterification reactor pre-containing reactants, a slurry prepared as follows is continuously fed: high-purity terephthalic acid (TPA) is used as the dicarboxylic acid component, and ethylene glycol (EG) and neopentyl glycol (NPG) are used as the diol components, with a total diol molar ratio (G / A) of 2.2 relative to the dicarboxylic acid component. The esterification reaction is then carried out under stirring at a pressure of 0.15 MPa and a temperature of 257°C, with an average retention time of 3 hours. The reactants are then transferred to a second esterification reactor, where esterification is carried out under stirring at a pressure of 0.05 MPa and a temperature of 257°C, with an average retention time of 1 hour. Finally, the esterified reactants are transferred to a third esterification reactor, where esterification is carried out under stirring at a pressure of 0.05 MPa and a temperature of 257°C.

[0087] Add neopentyl glycol and diethylene glycol in amounts equivalent to 20% of the amounts added before the esterification reaction to the generated oligomers to make them consistent with the target composition, and allow the reaction to proceed for at least 15 minutes.

[0088] In the esterification reaction product, a certain amount of ethylene glycol solution of aluminum compound (basic aluminum acetate) and ethylene glycol solution of phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added and continuously fed into the first polycondensation reactor. The mixture was stirred at 261°C and 6.7 kPa for 1 hour. Then, in the second polycondensation reactor, the mixture was stirred at 272°C and 0.6 kPa for 1 hour. Finally, in the final reactor, the polycondensation reaction was carried out at 275°C and 0.10–0.20 kPa for 1.4 hours with stirring. After the polycondensation reaction, the reactants were passed through a polymer filter, and the molten copolymer was taken out from the nozzle of the die head in a stranded shape. After being water-cooled in a cooling bath, it was cut into small pieces. A copolyester resin with a number average molecular weight of 29,000 was obtained. The evaluation results are shown in Table 1. The copolyester resin obtained in this embodiment was evaluated by sheet molding using method 8). It showed good formability, with a haze of 9.8 for the stepped molded sheet and a thermal stability of 0.11, which was found to be slightly reduced.

[0089] (Example 9) 2414 parts by weight of terephthalic acid (TPA), ethylene glycol (EG), neopentyl glycol (NPG), and diethylene glycol (DEG) were loaded into a 10L esterification reaction vessel equipped with a stirrer and a distillation condenser. An ethylene glycol solution of antimony trioxide and cobalt acetate as catalysts was added, so that the content of antimony metal was 250 ppm and cobalt metal was 10 ppm relative to the copolyester resin.

[0090] The temperature of the reaction system was then gradually increased until it reached 240°C, and the esterification reaction was carried out for 180 minutes at a pressure of 0.25 MPa. After confirming that there was no distillation from the reaction system, the reaction system was restored to atmospheric pressure, and neopentyl glycol and diethylene glycol, equivalent to 20% of the amount added before the esterification reaction, were added to the generated oligomer to match the target composition, and the reaction was carried out for at least 15 minutes. A trimethyl phosphate solution in ethylene glycol was added so that the residual phosphorus atoms contained in the generated copolyester were 50 ppm.

[0091] The obtained oligomers were transferred to a polycondensation reaction tank, and the temperature was gradually increased and the pressure reduced until the final temperature reached 270°C and the pressure was 0.2 hPa. The reaction was carried out until the torque value of the stirring blade corresponding to the intrinsic viscosity reached the desired value, thus explaining the polycondensation reaction. The resulting molten copolyester resin was extracted in a linear fashion from the outlet at the bottom of the polycondensation tank, cooled in a water bath, and then cut into small pieces. The number average molecular weight was 19,000. Heat treatment was performed in the same manner as in Example 1.

[0092] The results are shown in Table 1. In this embodiment, the obtained copolyester resin was evaluated by sheet molding using method 8). The formability was good, and the haze and thermal stability of the stepped molded sheet tended to be slightly worse, but there were no problems.

[0093] (Comparative Example 1) In a first esterification reactor pre-containing reactants, a slurry prepared as follows is continuously fed: high-purity terephthalic acid (TPA) is used as the dicarboxylic acid component, ethylene glycol (EG) is used as the diol component, and the molar ratio (G / A) of ethylene glycol to dicarboxylic acid is prepared to be 2.0. Then, the esterification reaction is carried out under stirring at a pressure of 0.17 MPa and a temperature of 255°C, with an average retention time of 3 hours. The mixture is then transferred to a second esterification reactor, where it is further esterified under stirring at a pressure of 0.05 MPa and a temperature of 261°C, with an average retention time of 1 hour. Finally, the esterified reactants are transferred to a third esterification reactor, where they are further esterified under stirring at a pressure of 0.05 MPa and a temperature of 266–267°C. A certain amount of ethylene glycol solution containing an aluminum compound (basic aluminum acetate) and an ethylene glycol solution containing a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were continuously fed into the first polycondensation reactor and stirred for 1 hour at 268°C and 4.7 kPa. Then, in the second polycondensation reactor, the mixture was stirred for 1 hour at 270°C and 0.57 kPa. Finally, in the final reactor, the polycondensation reaction was carried out for 1 hour at 274°C and 0.17 kPa with stirring. After the polycondensation reaction, the reactants were passed through a polymer filter, and the molten copolymer was taken out from the nozzle of the die head in a stranded form. After being water-cooled in a cooling bath, it was cut into small pieces. The number average molecular weight was 19,000. The evaluation results are shown in Table 1.

[0094] (Comparative Example 2) The NPG content was adjusted to 45 mol% using the same synthesis method as in Example 1, and the results were evaluated. Higher NPG levels resulted in poorer outcomes in all evaluations. The evaluation results are shown in Table 1.

[0095] (Comparative Example 3) Using the same synthesis method as in Example 1, the amount of DEG was adjusted to 30 mol% for synthesis, and the results were evaluated. Higher DEG concentrations resulted in poorer thermal stability. The evaluation results are shown in Table 1.

[0096] (Comparative Example 4) Using the same synthesis method as in Example 1, the amount of NPG was adjusted to 46 mol%, and the amount of DEG was adjusted to 23 mol%. The results were then evaluated. Higher levels of both DEG and NPG resulted in poor evaluation. The evaluation results are shown in Table 1.

[0097] (Comparative Example 5) In a first esterification reactor pre-containing reactants, high-purity terephthalic acid (TPA) was used as the dicarboxylic acid component, and ethylene glycol (EG) and neopentyl glycol (NPG) were used as the diol components. A slurry prepared by adjusting the molar ratio (G / A) of total diols to dicarboxylic acid components to 2.2 was continuously supplied. Diethylene glycol was added to match the target composition and continuously supplied to the first esterification reactor. The esterification reaction was then carried out under stirring at a reactor pressure of 0.15 MPa and a temperature of 257°C, with an average retention time of 3 hours. The reactants were then transferred to a second esterification reactor, where esterification was carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C, with an average retention time of 1 hour. Finally, the esterified reactants were transferred to a third esterification reactor, where esterification was carried out under stirring at a reactor pressure of 0.05 MPa and a temperature of 257°C. In the esterification reaction product, a certain amount of ethylene glycol solution of aluminum compound (basic aluminum acetate) and ethylene glycol solution of phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added and continuously fed into the first polycondensation reactor. The mixture was stirred at 261°C and 6.7 kPa for 1 hour. Then, in the second polycondensation reactor, the mixture was stirred at 272°C and 0.6 kPa for 1 hour. Finally, in the final polycondensation reactor, the mixture was stirred and subjected to a polycondensation reaction at 275°C and 0.10–0.20 kPa for 1 hour. After the polycondensation reaction, the reactants were passed through a polymer filter, and the molten copolymer was taken out from the nozzle of the die head in a stranded shape. After being water-cooled in a cooling bath, it was cut into small pieces. The number average molecular weight was 19,000. The evaluation results are shown in Table 1. The copolyester resin obtained in this comparative example was evaluated by sheet molding by method 8), and it was inferior to that of the examples.

[0098] [Table 1] Industrial availability

[0099] The copolyester resin of this invention has excellent transparency, color and formability, and rarely causes contamination of the molding die or foreign matter adhesion on the molded body and film. Therefore, it is excellent in terms of economy and can advantageously give the molded body a higher commercial value, making a great contribution to the industry.

Claims

1. A copolyester resin, characterized in that, When the main component of the dicarboxylic acid is terephthalic acid, the main component of the diol is ethylene glycol, and all diol components are set at 100 mol%, the content of neopentyl glycol is greater than 15 mol% and less than 40 mol%, the content of diethylene glycol is 9-20 mol%, the content of the cyclic dimer composed of terephthalic acid, neopentyl glycol and diethylene glycol is less than 5000 ppm, and the content of the cyclic trimer composed of terephthalic acid and ethylene glycol is less than 5000 ppm. The cyclic dimer is synthesized sequentially by bonds of terephthalic acid, neopentyl glycol, terephthalic acid and diethylene glycol. The cyclic trimer is synthesized by bonds of terephthalic acid and ethylene glycol in a cyclic manner of 3 alternating bonds. The number average molecular weight of the copolyester resin is 15000-29000.

2. The copolyester resin according to claim 1, characterized in that, The content of the cyclic trimer composed of terephthalic acid and ethylene glycol is below 4000 ppm.

3. The copolyester resin according to claim 1 or 2, characterized in that, The color b value of the copolyester resin is -5.0 to 10.

0.

4. The copolyester resin according to claim 1 or 2, characterized in that, The concentration of carboxyl terminus AV is 8~25 eq / t. The copolyester resin contains aluminum atoms and phosphorus atoms. The aluminum atom content in the copolyester resin is 15~40 ppm. The molar ratio of phosphorus atoms to aluminum atoms in the copolyester resin is 1.8~2.

6.

5. The copolyester resin according to claim 1 or 2, characterized in that, The haze value at a thickness of 5 mm for the stepped molded plate obtained by molding copolyester resin is less than 15%.

6. A molded article, characterized in that, It contains any one of the copolyester resins according to claims 1 to 5.

7. A heat-shrinkable film, characterized in that, It contains any one of the copolyester resins according to claims 1 to 5.

Citation Information

Patent Citations

  • Container made from copolyester

    JP1996337659A

  • Polyester resin and container-shaped molded product

    JP2000109546A

  • Copolyester resin and molded article thereof

    JP2004027176A

  • Copolymerized polyester

    JP2011046859A

  • Copolymerized polyester

    JP2011046860A